Developmental Co-expression of Vglut2 and Nurr1 in a Mes-Di-Encephalic Continuum Preceeds Dopamine and Glutamate Neuron Specification - Dumas, Sylvie; Wallén-Mackenzie, Åsa (Frontiers in Cell and Developmental Biology, 2019)
Midbrain dopamine (DA) neurons exist as several subtypes and are found in a heterogeneous environment including GABAergic and glutamatergic neurons as well as various types of co-releasing neurons. Developmental programs underlying this heterogeneity have remained elusive. In this study, combinatorial mRNA analysis was performed at stages when neuronal phenotypes are first specified. Vesicular transporters for dopamine and other monoamines (VMAT2), GABA (VIAAT), and glutamate (VGLUT2) were assessed by systematically applying fluorescent in situ hybridization through the mes-di-encephalon of the mouse embryo at embryonal days (E) 9.5–14.5. The results show that early differentiating dopamine neurons express the gene encoding VGLUT2 before onset of any dopaminergic markers. Prior to its down-regulation in maturing dopamine neurons, Vglut2 mRNA co-localizes extensively with Tyrosine hydroxylase (Th) and Nurr1, commonly used as markers for DA neurons. Further, Vglut2 and Nurr1 mRNAs are shown to overlap substantially in diencephalic neurons that maintain a glutamatergic phenotype. The results suggest that Vglut2/Nurr1-double positive cells give rise both to dopaminergic and glutamatergic neurons within the mes-di-encephalic area. Finally, analysis of markers representing subtypes of dopamine neurons, including the newly described NeuroD6 subtype, shows that certain subtype specifications arise early. Histological findings are outlined in the context of neuroanatomical concepts and the prosomeric model of brain development. The study contributes to the current decoding of the recently discovered heterogeneity among neurons residing along the cephalic flexure.